Design and Prickly Pear for a sustainable local Development - Anna Catania (Agathón)
The article describes the relationship between design and a Sicilian agro-food product, the Roccapalumba ficodindia (prickly pear), for economic and territorial development in the respect of the environment. In such that, prickly pear is considered a resource capable of launching innovations, like the exploitation of waste and the relationship between local people. In the article, to create a second life to waste, the life cycle of the prickly pear was studied and among the various outputs, it was considered the pruning of the cladodes from which fibre was obtained, used in an innovative way and according to a local vision, focusing on cultural heritage and traditions.